Anticoagulant Effect at the Time of Epidural Catheter Removal in Patients Receiving Twice-daily or Once-daily Low-molecular-weight Heparin and Continuous Epidural Analgesia after Orthopedic Surgery - Douketis, James D.; Kinnon, Krystyna; Crowther, Mark A. (Thrombosis and Haemostasis, 2002)
In patients who receive co-administered low-molecular-weight heparin (LMWH) and continuous epidural analgesia (CEA) after orthopedic surgery, there is concern about an increased risk of a spinal epidural hematoma. The practice of twice-daily LMWH dosing in North America might, in part, account for the greater number of epidural hematomas reports compared to Europe where once-daily LMWH is used. We performed a prospective cohort study in patients who had orthopedic surgery and received co-administered LMWH and CEA. We investigated the trough anticoagulant effect, as measured by an anti-Xa heparin level, at the time of epidural catheter removal in patients who received twice-daily or once-daily LMWH. Twenty-five patients who received enoxaparin, 30 mg twice-daily, and 25 patients who received dalteparin, 5,000 IU once-daily, had anti-Xa heparin levels measured on the second or third post-operative day at the time of epidural catheter removal. In patients who received twice-daily enoxaparin, or once-daily dalteparin, the anti-Xa heparin level was measured, on average, 10.4 h and 21.8 h, respectively, after the preceding LWMH dose. All 25 patients who received once-daily LMWH had an anti-Xa heparin level <0.10 U/ml at the time of catheter removal. Of 25 patients who received twice-daily LMWH, the anti-Xa heparin level at the time of catheter removal was >0.20 U/ml in 5 patients (P = 0.050), and >0.10 U/ml in 7 patients (P = 0.009). We conclude that in patients who are receiving co-administered LMWH and CEA after orthopedic surgery, twice-daily but not once-daily LMWH administration is more likely to be associated with a clinically important anticoagulant effect at the time of epidural catheter removal.
Keywords: Low-molecular-weight heparin; epidural analgesia; bleeding; thrombosis